(untitled) (Raparin Journal of Humanities (RJH), 2026)
The primary objective of this study is to explore the relationship between future anxiety and academic Performance among students at Raparin University, as well as to examine the role of demographic variables (gender and specialization) on the study outcomes. To achieve these objectives, the researchers employed a descriptive "correlational" methodology. The researchers developed a standardized form consisting of a future anxiety scale with 24 items and an academic achievement scale with 25 items, with complete psychometric properties conducted for both scales. Subsequently, the scale form was distributed using stratified random sampling to )360(students at Raparin University, of which 194 were male and 166 were female. For analyzing the collected data, the researchers utilized the Statistical Package for Social Sciences (SPSS). The most significant findings of this study include: Generally, future anxiety is at a moderate level, while academic Performance is at a low level. Furthermore, it was found that professional and economic future anxiety is higher among males compared to females; however, regarding "health and fear of death" future anxiety, it is higher among females compared to males. Additionally, academic Performance is higher among females compared to males. It was also revealed that students specializing in humanities and social sciences have higher future anxiety compared to students specializing in natural and applied sciences. However, specialization differences had no significant impact on academic achievement levels. Finally, it was found that there is no statistically significant relationship between future anxiety and academic Performance t.